Second harmonic suppression characteristic of a grooved bandpass filter - Marimuthu, , Jayaseelan; Esa, , Mazlina (2005)
In analysing the performance of any communication system, degradation is usually caused by unwanted signals. Filters are hence placed at desired locations to filter out these unwanted frequencies. However, the presence of significant harmonic signals that can be generated by devices such as mixers can easily contribute to the unwanted frequencies. Special attention has to be given in suppressing the second harmonic present in the filter output. This paper presents the design of a parallel-coupled bandpass filter having grooved structures. The chosen frequency of operation is 2.5 GHz, suitable for wireless communication system. The proposed design improvements were investigated for Chebyshev response filters. The filters consist of several filter orders, each having different number of grooves. Experimental investigations revealed that as the number of grooves increases, the second harmonic signal decreases. However, it is interesting to note that the behaviour changed with the presence of seven grooves.